First record of occurrence and injury of Anomala testaceipennis Blanchard, 1851 (Coleoptera: Scarabaeidae: Rutelinae) in arabica coffee in Brazil - Souza, Antônio S.; Silva, Maria G.; Fernandes, Maria E. S.; Nascimento, Antonio G. O.; Silva, Pamela F.; Rodrigues, Sergio R.; Fernandes, Flávio L. (Entomological Communications, 2023)
The objective of this study is to record the injury of Anomala testaceipennis Blanchard, 1851 (Coleoptera: Scarabaeidae: Rutelinae) adults in coffee Coffea arabica L. in municipality of Piumhi, Minas Gerais, Brazil. This is the first reported of the A. testaceipennis attacking coffee.